Managing the new organization: some problems of institutional transition - a New Zealand perspective - Aitken, Judith (1997)
The article presents a policy-maker's view of one of the most radical and most-consistently sustained policy and institutional reforms. It begins by reviewing factors affecting the nature and tempo of New Zealand's reform initiatives, including `woodenheadedness', the political capacity to deliver sustained economic change, the failure of universities and other centres of research and scholarship to generate new ideas; the resistance of entrenched systems; the significance of generating a popular conceptual framework for reform in a literate, articulate society. Issues that are relevant in implementing policy initiatives include: the scarcity of competent managers, particularly associated with the country's small scale; the impact of geography and technology; timing and queuing; loss of institutional memory; the power of communication to fail; and the persistence of ideological, professional ways of thinking, backed by the power of unions and professional associations. This article surveys essential concepts and elements of New Zealand's state sector reforms, focusing on: the guiding philosophy - transparency and consistency; operating principles - the distinction between outputs and outcomes, purchaser and provider, government and departments; the principal instruments - purchase agreements between ministers and chief executives, delegation, performance measures. - Reproduced
Keywords: Public sector - New Zealand; Administrative reform